Anesthesiology in the Lisbon Military Hospital - Lufinha, Ana; Rodrigues, Fernando Matos; Mateus, Artur Pinto de Magalhães; Tavares, Jorge (Journal of the Portuguese Society of Anesthesiology, 2014)
Anaesthesia practice by surgeons at the Military Hospital in Lisbon started at 1848, soon after its introduction in Europe. After Second World War, improvements in anaesthesia practice were introduced. Anaesthesia was experimentally organized as a Service, integrated into the Surgery Service by the end of the last century 50’s. Later (1961) it was recognized as an autonomous service of Anaesthesiology, with a specific preoperative assessment clinic and a recovery room. The Portuguese Colonial War began in Angola (1961), Guinea-Bissau (1963) and Mozambique (1964), lasting for 13 years. As consequence, the main Military Hospital in Portugal suffered a deep modification in the number of surgeries, namely in Traumatology and Plastic Surgery and in the patient risk, largely related to difficult airways. The Service was involved in an accelerated process of education of nurses and anaesthesiologists for the military hospitals in Africa.